InterCorp and Treq as Tools Facilitating the Search for Equivalents - Kaczmarska, Elżbieta (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article is devoted to disambiguation tools which may be helpful in solving the problem of understanding and translating ambiguous words, particularly verbs denoting emotional and mental states. The study offers an introduction to InterCorp, a multilingual parallel corpus currently covering 41 languages, and provides technical advice on text access and search. It also outlines the idea and genesis of the application called Treq as well as the mechanism of its operation. Using InterCorp and Treq, the author conducts an analysis aiming to find the Polish equivalent for the Czech verb mrzet.